Dermolipectomy for severe abdominal lipodystrophy in morbid obesity - Fernández, Elena A.; Acevedo, Víctor E.; D’Angelo, María A.; Ayala, Lucrecia M.; Ruiz, Matías E. (Revista Argentina de Cirugía, 2026)
Overweight and obesity are defined as abnormal or excessive fat accumulation that presents a risk to health. It is a chronic disease caused by multiple factors, which results in hygienic issues, functional disability and impaired quality of life. Abdominal dermolipectomy is the only surgical option for the treatment of patients with prominent panniculus morbidus, thus reducing complications and providing social reintegration for the patient who has been limited for many years due to the enormous abdominal panniculus. We report the case of a 53-year-old female patient with severe abdominal lipodystrophy with coverage of both ankles, skin involvement, and disability to perform daily activities, that was managed with abdominal dermolipectomy and resection of 29 kg of dermo-adipose tissue. Bibliographic research is also presented.